Planning for talent gymnasts. A case study in Barcelona (Spain) - Irurtia, A.; Gutierrez, J.; Marina, M.; Busquets, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The bioenergetic research in gymnastics, is conditioned first of all by the characteristics of a technical-combinatory sport, where the variability of the performance factors is higher and more complex than in other sports [1;5]. In the past 40 years, the physiological profile of the elite gymnast has evolved towards better anaerobic power, oxygen consumption, HR values, and energetic cost [4]. The reason seems to be, on the one hand, the longer duration in competition exercise, due to the increase in elements, both in number and difficulty, and on the other, the improvement of the reliability and validity of the different instruments [4]. Despite this, numerous authors reject the HR as a valid indicator to plan the training in this sport, mainly because of the large intrasubject variability reflected over a whole season. Emotional factors previous to the motor action may cause an anticipatory behaviour due to a preadaptation of the sympathetic neural system accompanied by a hyperactive hormonal context [2]. Nevertheless the usefulness of HR increases when we have to control the training system. This study proposes: 1) criteria to quantify the internal load using HR values with young beginners, 2) a logical sequence to train this population, 3) to establish the theoretical basis during their first stage of training. Methods We describe a planning model applied during the season 2000/01 to a group of young (8 ± 1 years) male gymnasts (n = 10), selected for high performance training. The program is structured by "Logical Significant Blocs" (LSB). The term LSB used in this study has been chosen for the following reasons: 1) Significant: because of the degree of objectivity of the internal load quantification criterium, where the intensity can be estimated from the HR profile of each gymnasts' LSB 2) Logical: the LSB sequence follows a logical model of planning, which is dynamic, open, and evolves with time. They have an external logic (from one bloc to another) and an internal one (within its own contents). We chose the formula "I1 = P / T" [3] to be the most accurate expression to calculate the external load in our group. The HR is registered by pulsometers. To validate and calculate the liability of the model, we used the ICC and Pearson coefficient correlation between similar LSBs. Results and Discussion From the training and planning model presented in this study it is observed that the intensity remains quite constant, the volume being the most changing factor. When volume decreases, the intensity does likewise. This is because our goal is not to reach "optimal fitness", but to reduce physical and psychological stress. The performance curve has a high motivational character, because the psychological load acts as a positive stimulus in the child. This is possible thanks to a long-term strategy, considering the early initiation as well as the duration (fro childhood to adulthood) and the demands of a competitive sport such as gymnastics.